EFFECT OF THE DISTANCES BETWEEN SUBSOILER PLOW TINES BILATERAL AND PENETRATION ANGLES ON SOME PERFORMANCE INDICATORS FIELD - Adel Abdullah; Yousif Y. Hilal (Mesopotamia Journal of Agriculture)
The research was implemented in a field of agriculture college- Mosul Univ., which its soil texture is clay. The study included the use of three penetration angles of subsoiler plow tines bilateral 30 and 40 and 50 degree and three distances between subsoiler plow tines bilateral 1.1 and 1.5 and 1.75 meters and Forward Speed of the tractor 2.37 and 3.50 km / h and its impact on Draw-bar Power, Slippage , Specific resistance , tillage width at the surface and stability Ratio of the depth. The experiment was conducted by using Randomized Complete Block Design RCBD. Three factors was used with its interactions. The use of Duncan multiple range test to indicate significant differences between the averages of the transactions, The results showed that all the traits affected by moral penetration angles and distances between subsoiler plow tines and Forward Speed of the tractor in terms of increased Draw-bar Power, Slippage , Specific resistance at increase penetration angles and Forward Speed of the tractor and lower tillage width at the surface and stability Ratio of the depth. The distance between the tines was 1.5 meters ranked first in the devaluation of the Draw-bar Power, Slippage , Specific resistance and increased tillage width at the surface and stability Ratio of the depth. Give an interactions distance of 1.5 meters and the angle of penetration of 30 degrees and Forward Speed of the tractor 2.37 km/h. The best results in reducing the Draw-bar Power, Slippage , Specific resistance and the values ​​are respectively 8.06 Kw and 5.07% and 39.89 Kn / m 2 and gave the highest tillage width at the surface and stability Ratio of the depth values which ​​were 156.67 cm and 93.34% respectively.